Intersection of Lincoln and Minnesota Avenues in Willow Glen - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Street view of the intersection of Lincoln and Minnesota Avenues in Willow Glen. On the left stands the Willow Glen School. On the far right stands an automobile service station and Gordon's gocery store. The pronounced speckling located on the far left side of the image is due to the degredation of nitrate film.